Deficiency of myeloid PHD proteins aggravates atherogenesis via macrophage apoptosis and paracrine fibrotic signalling. Issue 5 (29th April 2021) - van Kuijk, Kim; Demandt, Jasper A F; Perales-Patón, Javier; Theelen, Thomas L; Kuppe, Christoph; Marsch, Elke; de Bruijn, Jenny; Jin, Han; Gijbels, Marion J; Matic, Ljubica; Mees, Barend M E; Reutelingsperger, Chris P M; et al.
Abstract: Aims: Atherosclerotic plaque hypoxia is detrimental for macrophage function. Prolyl hydroxylases (PHDs) initiate cellular hypoxic responses, possibly influencing macrophage function in plaque hypoxia. Thus, we aimed to elucidate the role of myeloid PHDs in atherosclerosis. Methods and results: Myeloid-specific PHD knockout (PHDko) mice were obtained via bone marrow transplantation (PHD1ko, PHD3ko) or conditional knockdown through lysozyme M-driven Cre recombinase (PHD2cko). Mice were fed high cholesterol diet for 6–12 weeks to induce atherosclerosis. Aortic root plaque size was significantly augmented 2.6-fold in PHD2cko, and 1.4-fold in PHD3ko compared to controls but was unchanged in PHD1ko mice. Macrophage apoptosis was promoted in PHD2cko and PHD3ko mice in vitro and in vivo, via the hypoxia-inducible factor (HIF) 1α/BNIP3 axis. Bulk and single-cell RNA data of PHD2cko bone marrow-derived macrophages (BMDMs) and plaque macrophages, respectively, showed enhanced HIF1α/BNIP3 signalling, which was validated in vitro by siRNA silencing. Human plaque BNIP3 mRNA was positively associated with plaque necrotic core size, suggesting similar pro-apoptotic effects in human. Furthermore, PHD2cko plaques displayed enhanced fibrosis, while macrophage collagen breakdown by matrix metalloproteinases, collagen production, and proliferation were unaltered. Instead, PHD2cko BMDMs enhanced fibroblast collagen secretion in a paracrine manner. In silico analysis of macrophage-fibroblast communication predicted SPP1 (osteopontin) signalling as regulator, which was corroborated by enhanced plaque SPP1 protein in vivo . Increased SPP1 mRNA expression upon PHD2cko was preferentially observed in foamy plaque macrophages expressing 'triggering receptor expressed on myeloid cells-2' (TREM2hi) evidenced by single-cell RNA, but not in neutrophils. This confirmed enhanced fibrotic signalling by PHD2cko macrophages to fibroblasts, in vitro as well as in vivo . Conclusion: Myeloid PHD2cko and PHD3ko enhanced atherosclerotic plaque growth and macrophage apoptosis, while PHD2cko macrophages further activated collagen secretion by fibroblasts in vitro, likely via paracrine SPP1 signalling through TREM2hi macrophages. Graphical Abstract: